2022
DOI: 10.1111/spol.12806
|View full text |Cite
|
Sign up to set email alerts
|

No activation without reconciliation? The interplay between ALMP and ECEC in relation to women's employment, unemployment and inactivity in 30 OECD countries, 1985–2018

Abstract: Comparative welfare state research as examined the outcomes of active labour market policies (ALMP) and work‐family reconciliation policies by and large been separately. As a result, potential complementarities between these policy areas have received scant attention empirically. Using macro‐level data, this study answers the question to what extent, and in which way, governments' efforts in ALMP and in early childhood education and care (ECEC) services are complementary to each other in promoting women's empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 60 publications
2
24
0
Order By: Relevance
“…Hemerijck et al (2016) showed that the positive association between investments in ALMPs and employment is stronger when investment in ECEC services is higher, especially for specific risk groups. Similar findings have more recently been exposed by Nieuwenhuis (2022) on the complementary nature of ALMP and ECEC policies on female employment. Bakker and Van Vliet (2021) found diminishing marginal returns between the same two policies.…”
Section: Establishing Macro Regularitiessupporting
confidence: 84%
See 4 more Smart Citations
“…Hemerijck et al (2016) showed that the positive association between investments in ALMPs and employment is stronger when investment in ECEC services is higher, especially for specific risk groups. Similar findings have more recently been exposed by Nieuwenhuis (2022) on the complementary nature of ALMP and ECEC policies on female employment. Bakker and Van Vliet (2021) found diminishing marginal returns between the same two policies.…”
Section: Establishing Macro Regularitiessupporting
confidence: 84%
“…Inclusive buffers, for example, aim at reducing poverty, but can also ease the labour market flow by improving job matching and reducing skill depletion (Gangl, 2006). Childcare services are aimed at boosting human capital stock, but can also facilitate labour market flows (Plavgo and Hemerijck, 2021;Nieuwenhuis, 2022). However, it should be recognized that stock, flow and buffer policy considerations are subject to highly diverse socio-economic dynamics.…”
Section: A Working Definition Of Social Investment In Terms Of Comple...mentioning
confidence: 99%
See 3 more Smart Citations